2017
DOI: 10.21873/anticanres.11411
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells in Mammary Carcinogenesis: Host or Tumor Supporters?

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The relationship between MC density of tumors, the progression of angiogenesis, and tumor development may highlight the possible role of MCs in tumor biology. Therefore, the possibility of targeting MC activation [67,68], inhibiting the release of mediators using c-Kit receptor tyrosine kinase inhibitors (TKI) (including imatinib, masitinib [69]), or using tryptase inhibitors (mainly gabexate mesylate and nafamostat mesylate, both inhibitors of trypsin-like serine proteases [69,70]) may be valuable therapeutic approaches to control the tumor development [71]. Masitinib, a TKI that targets c-kit receptors (CD117), has been used in veterinary medicine for years, and lately, human clinical trials were initiated to test its clinical efficacy as single or add-on treatment human cancers such as mastocytosis, gastrointestinal stromal tumors (NCT00998751), colon cancer (NCT03556956), prostate cancer (NCT03761225), and pancreatic cancer (NCT03766295) [72].…”
Section: Mcs As Therapeutic Targetsmentioning
confidence: 99%
“…The relationship between MC density of tumors, the progression of angiogenesis, and tumor development may highlight the possible role of MCs in tumor biology. Therefore, the possibility of targeting MC activation [67,68], inhibiting the release of mediators using c-Kit receptor tyrosine kinase inhibitors (TKI) (including imatinib, masitinib [69]), or using tryptase inhibitors (mainly gabexate mesylate and nafamostat mesylate, both inhibitors of trypsin-like serine proteases [69,70]) may be valuable therapeutic approaches to control the tumor development [71]. Masitinib, a TKI that targets c-kit receptors (CD117), has been used in veterinary medicine for years, and lately, human clinical trials were initiated to test its clinical efficacy as single or add-on treatment human cancers such as mastocytosis, gastrointestinal stromal tumors (NCT00998751), colon cancer (NCT03556956), prostate cancer (NCT03761225), and pancreatic cancer (NCT03766295) [72].…”
Section: Mcs As Therapeutic Targetsmentioning
confidence: 99%
“…Many studies showed that the transduction activities induced by histamine receptors include a variety of intracellular signaling pathways [18]. Interestingly, the expression of histamine receptors has been detected in many tumor cells, making them sensitive to histamine stimulation and contributing to tumor development [6]. Here, we compared the expression of different histamine receptors between normal skin tissues and AIDS-KS tissues by using IHC staining.…”
Section: Resultsmentioning
confidence: 99%
“…Histamine is mainly produced and released by mast cells (MCs), acting as a bivalent regulator for cancer development [6]. Histamine, together with its receptors, plays an important role in various allergic diseases by regulating different inflammation and immune responses [7].…”
Section: Introductionmentioning
confidence: 99%
“…These findings may form the basis for a further evaluation of the clinical usefulness of histone methyltransferase inhibition for the treatment of conditions characterized by mast cell transformation, such as mastocytosis. We can also foresee the use of methyltransferase inhibition in malignant conditions where mast cells might have a pathogenic impact (46).…”
Section: Discussionmentioning
confidence: 99%